Checklist of the Hoverflies (Diptera: Syrphidae) of Slovenia - De Groot, Maarten (Acta entomologica slovenica (Ljubljana), 2008)
A checklist of the hoverflies (Diptera: Syrphidae) of Slovenia is compiled. Until now, the hoverfly fauna of Slovenia has been poorly known and existing information scattered in journals and collections throughout Europe. The checklist is based on records extracted from 35 articles and twelve collections, supplemented by two years of fieldwork. In total 274 species are listed, 109 of the subfamily Syrphinae, 162 of the Eristalinae and 3 of the Microdontinae.
Keywords: entomologija; favna; muhe; muhe trepetavke; Slovenia; Slovenija